2013
DOI: 10.1001/jamainternmed.2013.3254
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Content of Dietary Supplements Consumed on Military Bases

Abstract: The initial Group Visits Trial was led by Dr Edelman (principal investigator), Morris Weinberger, PhD (co-principal investigator), and Sonja K. Fredrickson, MD (site principal investigator). Cynthia J. Coffman, PhD, provided an important review of an earlier draft of the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 7 publications
0
18
0
2
Order By: Relevance
“…We only determined the quantity of BMPEA in Acacia rigidula supplements. It is possible that caffeine and other stimulants might be present in these supplements, potentially increasing the risks these supplements pose to consumers . In fact, European investigators have found an analogue of methamphetamine, N,N‐dimethyl‐2‐phenylpropan‐1‐amine (DMPPA) combined with in BMPEA in the same dietary supplement (i.e., NOXPUMP) .…”
Section: Resultsmentioning
confidence: 99%
“…We only determined the quantity of BMPEA in Acacia rigidula supplements. It is possible that caffeine and other stimulants might be present in these supplements, potentially increasing the risks these supplements pose to consumers . In fact, European investigators have found an analogue of methamphetamine, N,N‐dimethyl‐2‐phenylpropan‐1‐amine (DMPPA) combined with in BMPEA in the same dietary supplement (i.e., NOXPUMP) .…”
Section: Resultsmentioning
confidence: 99%
“…Con cern regarding the possibility of caffeine toxicity arising from supplement use among soldiers has previously been raised. 5 Motivations to the use of supplements and exercise were illuminating in the predominance of physical appearance in the responses. Requirements of military missions and limited dietary choices were described as among the top three most commonly identified motivations to exercise and use supple ments.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Bitkisel zayıflama ürünlerinin içeriklerinde yer aldığı belirtilen maddeler dışında, tiroid hormonları, diüretik-ler, laksatifler, kafein, sempatomimetikler ve sibutramin gibi çok çeşitli ilaç etken maddeleri bulunabildiği araştır-malarla gösterilmiştir. [10][11][12] Bitkisel zayıflama ürünlerinin içeriğinde belirtilmeyen bu aktif ilaçlar çeşitli yan etkilere, hatta ölüme bile neden olabilmektedirler. 3,9 Ülkemizden de Özdemir ve ark.…”
Section: Discussionunclassified